A Systematic Literature Review on Traumatic Optic Neuropathy - Saeed Karimi; Amir Arabi; Iman Ansari; Toktam Shahraki; Sare Safi (Journal of Ophthalmology)
Traumatic optic neuropathy (TON) is an uncommon vision-threatening disorder that can be caused by ocular or head trauma and is categorized into direct and indirect TON. The overall incidence of TON is 0.7–2.5%, and indirect TON has a higher prevalence than direct TON. Detection of an afferent pupillary defect in the presence of an intact globe in a patient with ocular or head trauma with decreased visual acuity strongly suggests TON. However, afferent pupillary defects may be difficult to detect in patients who have received narcotics that cause pupillary constriction and in those with bilateral TON. Mechanical shearing of the optic nerve axons and contusion necrosis due to immediate ischemia from damage to the optic nerve microcirculation and apoptosis of neurons is a probable mechanism. The proper management of TON is controversial. High-dose corticosteroid therapy and decompression of the optic nerve provide no additional benefit over observation alone. Intravenous erythropoietin may be a safe and efficient treatment for patients with TON.